Analysis of Creative Jewelry Products, Mutiara City, Mataram in The Context Of Customer Satisfaction - Muhamad Ilhamudin; Rusminah HS (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to determine consumer satisfaction for creative product produced by the Sekarbela pearl jewelry industry center in Mataram city. The type of research is descriptive, which is used to get an overview from an analysis of various attributes attached to pearl jewelry.This study uses a sample survey method. The population were all consumers of creative pearl jewelery products who came to industrial centers to make purchases. The respondent determination technique used was purposive sampling. The number of samples taken were 100 people.To answer the problem formulated, the analytical tool used is the Consumer Satisfaction Index (IKK) model. This model is to measure the difference between what consumers want and feel. The results showed that consumers were very satisfied with the creative pearl jewelery products produced by the Sekarbela creative industry center in the city of Mataram. However, marketers should always evaluate the context of the attributes that build this satisfaction because consumer satisfaction is very tentative.